A content analysis of news on H1N1 influenza in selected newspapers in Malaysia / Ismail Sualman and Amelia Abdul Aziz - Sualman, Ismail; Abdul Aziz, Amelia (Universiti Teknologi MARA, Shah Alam, 2012)
The spreading of the H1N1 flu popularly known as "swine flu" is a deadly threat to human life. However, unlike the typical "swine flu," H1N1 flu spreads quickly and easily as it contains genetic materials from human, swine and avian flu viruses. In June 2009, when the infections widen worldwide, the World Health Organization declared H1N1 flu a global pandemic. Malaysia recognized its risk as one of the countries with a high probability of an epidemic as it borders countries such as Thailand, Singapore, Cambodia and etc.. These were the countries that were experiencing the outbreak at that time. Therefore, this research is aimed to examine how issues attached to H1N1 flu are conveyed to or by the three leading Malay newspapers (Utusan Malaysia, Berita Harian and Sinar Harian). A content analysis was conducted on 150 randomly selected news articles published from May to October 2009. The study focused on the concepts of agenda-setting and framing. The Agenda Setting theory hypothesizes that there is a correspondence between the order of importance given in the media to 'issues' and the order of significance attached to the same issue by the public and the government. Likewise, media framing suggests that the media not only set the agenda on specific issues, events, or candidates but also transfer the salience on specific attributes belonging to those potential objects of interest. The findings revealed the need for awareness and intervention campaigns to improve the Malaysian